Hubungan Obesitas Dengan Keteraturan Siklus Menstruasi Pada Remaja - Siti Santika Kusuma Wardani; Winarni Winarni (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Background; Menstruation is bleeding that occurs when the uterine lining sheds. One of the factors that cause menstrual cycle irregularities is being overweight. According to the Surakarta City Health Profile, there were 8,889 cases of obesity in 2021, an increase compared to 2020 with 5,384 cases. In obese women there is an increase in estrogen production which causes an increase in androgen hormones, which can affect the development of mature follicles. Objective; This study aims to determine the relationship between obesity and menstrual cycle regularity. Method; Analytical observational research with a cross sectional research design. The population of all midwifery students at `Aisyiyah University Surakarta, totaling 142 students with a sample size of 59 respondents, used a purposive sampling technique. Primary data refers to the questionnaire sheet. The data obtained were analyzed using the Chi-Square statistical test. Results; The results showed that the analysis of the relationship between obesity and the regularity of the menstrual cycle using the Chi-Square test obtained p = 0.047. This figure is smaller than ? = 0.05, which means that there is a significant relationship between obesity and the regularity of the menstrual cycle of undergraduate students in Midwifery at `Aisyiyah University, Surakarta. The results of the Odds Ratio (OR) were also obtained at 3.187. This states that obesity increases the risk factor for irregular menstrual cycles up to 3.187 times. Conclusion; There is a relationship between obesity and the regularity of the menstrual cycle in adolescents.